Pengembangan Model Promosi UMKM Kerajinan Jahit Pakaian Berbasis Teknologi E-Commerce Menggunakan Opencart untuk Memperluas Pasar di Kab. Agam - Putri, Rahma Yulia; Annas, Firdaus; Zahra, Anisa (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This research aims to develop a technology-based promotion model for Micro, Small and Medium Enterprises (MSMEs) of clothing sewing crafts based on e-commers technology using openchart to expand the existing market in Agam Regency. This research is motivated by the fact that MSMEs often face challenges in marketing their products, especially in the limitations of wider market access, the low use of digital technology in promotion, and the lack of knowledge of MSME actors about effective online store management. MSMEs in this area should use and utilize modern e-commers technology to develop more modern and efficient promotional strategies so that their products can be recognized by a wider market. Where by using openchart they can offer affordable solutions with various features that can be customized to meet the specific needs of local MSMEs, save costs, are effective and also user-friendly to develop product viability and support business growth. However, many MSME players do not have the understanding and resources to implement digital platforms optimally. This research uses the Research and Development (R&D) method with the Define, Design, Develop, Decemination development model. The results of this study are in the form of a web-based promotional media using openchart applications that are valid, practical and effective, where the use of openchart as a promotional platform has a positive impact, especially in increasing efficiency in marketing products, increasing sales, expanding market reach and business management. The findings of this study are that openchart can be used as a craft promotion media to increase the competitiveness of MSME products in Agam Regency.